TRADISI MESAMBAKAY PADA KOMUNITAS ADAT TOLAKI-MEKONGGA (Studi Etnografi di Kabupaten Kolaka) - diah, mohammad; Bahtiar, Bahtiar; Topo Jers, La Ode (Jurnal Penelitian Budaya, 2021)
The research questions of this research are as follows: (1) How is the process of implementing mesambakay in Tolaki-Mekongga indigenous community in Kolaka Regency? (2) What is the symbolic meaning of mesambakay in the Tolaki-Mekongga customary community in Kolaka Regency? The objectives of this research are to: (1) know and explain the mesambakay process in Tolaki-Mekongga customary community in Kolaka Regency, (2) explain the symbolic meaning of mesambakay in the Tolaki-Mekongga customary community in Kolaka Regency. This research method uses ethnographic method with a qualitative approach as a research procedure that produces descriptive data in the form of written or oral explanations of people and observable behavior. The data analysis technique used in this study is in accordance with the statement expressed by Miles and Huberman (2009: 16-20) which states that data analysis activities in qualitative research consist of three stages carried out simultaneously, namely Data Reduction, Data Presentation and Conclusion. The results of this study indicate that: (1) The process of implementing the mesambakay ritual in the Tolaki-Mekongga customary community in Kolaka District shows a tradition that is continuously carried out by the people of Kolaka Regency, especially in Wundulako District. In practice, it turns out that the mesambakay ritual depicts a tradition of "asking God for prayer" for the first child (iliwua) aged 40 days to the age of 2 years to be given strength, health and a better life. (2) The symbolic meaning of mesambakay in the Tolaki-Mekongga customary community in Kolaka Regency shows the existence of human interaction, interaction with the surrounding environment and interaction with God, so that the meaning comes from several symbols of tools and materials used in mesambakay rituals such as bamboo ( kowuna), a food container (siwole), a headband (kinawo), leaves (laughter), a coconut shell (ullo), and a pair of chickens (omanu). Thus, it can be concluded that the Mesambakay Tradition in the Tolaki-Mekongga indigenous community (Ethnographic Study in Wundulako Subdistrict, Kolaka Regency) is continuously carried out and has become one of the traditions in strengthening the ties of friendship between communities in Kolaka Regency.Key words: Mesambakay tradition, Tolaki-Mekongga indigenous community